From trafficking to terror: constructing a global social problem - Mahdavi, Pardis (Framing 21st century social issues, 2014)
Series forward -- Preface -- Acknowledgments -- Chapter abstracts -- Prologue: producing panic, pleading for power -- Trafficking terror, terrorizing trafficking -- Colliding wars -- Interrogating the illicit -- Living the wars on terror and trafficking -- Conclusion : towards a new paradigm -- References -- Glossary/index